2019
DOI: 10.1097/aog.0000000000003504
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain and Adverse Birth Outcomes in Twin Pregnancies

Abstract: The solid lines represent the point estimate and dashed lines represent its 95% confidence bands. Outcomes are preterm birth <32 weeks (orange lines), small-for-gestational-age birth (green lines), large-for-gestational-age birth (purple lines), and infant death (blue lines). Risks were set at the population average for maternal race/ethnicity, maternal education, maternal age, marital status, parity, insurance source, smoking during pregnancy, pre-existing diabetes or hypertension, height, prepregnancy weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 47 publications
2
71
1
Order By: Relevance
“…In addition, our study provided reliable results through multivariate analysis of factors such as maternal outcomes through binary logistic regression and neonatal outcomes by the GEE. Although the gestational age at birth, chorionicity, and fetal sex are important variables that can lead to adverse outcomes, many previous studies did not correct for them [34,[36][37][38][39]. In addition, GEE analysis, which is a method used to adjust for the correlation between twins, was not performed in previous studies despite its necessity [22,34,36,39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study provided reliable results through multivariate analysis of factors such as maternal outcomes through binary logistic regression and neonatal outcomes by the GEE. Although the gestational age at birth, chorionicity, and fetal sex are important variables that can lead to adverse outcomes, many previous studies did not correct for them [34,[36][37][38][39]. In addition, GEE analysis, which is a method used to adjust for the correlation between twins, was not performed in previous studies despite its necessity [22,34,36,39].…”
Section: Discussionmentioning
confidence: 99%
“…Bodnar et al 51 found the association between self-reported pre-pregnancy BMI and pregnancy outcomes was overestimated without considering misclassification. However, Momoli et al 50 and Bodnar et al 52 reported that the observed relationship did not change markedly after applying PBAM compared to conventional methods.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies applied this method in other contexts. [50][51][52][53][54][55] For example, De Silva et al 53 found a stronger association between the risk of maternal transfusion and inter-pregnancy interval after adjusting for misclassification of severe maternal morbidity. Bodnar et al 51 found the association between self-reported pre-pregnancy BMI and pregnancy outcomes was overestimated without considering misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…In this tertiary care center, many studies have investigated the effects of single maternal risk factors such as diabetes mellitus, antenatal coverage, small for gestational age, cesarean delivery, malpresentation, and body mass index on pregnancy outcomes [ 9 - 11 ]. However, the antenatal risk score, which is multifactorial, is not only an educational tool but also a comprehensive assessment of potential pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%